PENERAPAN TEKNOLOGI DIVERSIFIKASI OLAHAN SUSU DI KELOMPOK USAHA OMAH COWBOY DESA BANYUANYAR, KABUPATEN BOYOLALI - Mufidah, Kholifia Ahsanul; Barokah, Aprilia Nur; Sultoni, Tasya Putri; Ramadana, Alvin Ishafa; Budiati, Aprilania Eko; Nirindra, Aulia Sophie; Hertanto, Bayu Setya (Universitas Padjadjaran, 2025)
One of the keys to success in strengthening the village economy is capitalizing on local resources. Banyuanyar Village has the highest cow’s milk production in Boyolali Regency, which presents an opportunity to improve the community’s economy by converting cow’s milk into various processed products. The extension and training activities on dairy product diversification technology (milk tofu and milk sticks) for the